2008
DOI: 10.1038/sj.clpt.6100452
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Antiretroviral Regimen Containing Ritonavir Boosted Lopinavir on Intestinal and Hepatic CYP3A, CYP2D6 and P-glycoprotein in HIV-infected Patients

Abstract: (2008). Effect of an antiretroviral regimen containing ritonavir boosted lopinavir on intestinal and hepatic CYP3A, CYP2D6 and P-glycoprotein in HIV-infected patients. Clinical Pharmacology and Therapeutics, 84 (1) This study aimed to quantify the inhibition of CYP3A, CYP2D6 and P-glycoprotein in HIVinfected patients receiving an antiretroviral therapy containing ritonavir boosted lopinavir, and to identify factors influencing ritonavir and lopinavir pharmacokinetics.We measured activities of CYP3A, CYP2D6 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 46 publications
(98 reference statements)
5
67
0
Order By: Relevance
“…Similar conclusions were articulated previously (van Heeswijk et al, 2006) and also were reached using oral digoxin, considered to quantify primarily intestinal P-gp activity (Wyen et al, 2008). Ritonavir-lopinavir increased digoxin AUC and C max 1.8-and 1.6-fold, respectively, interpreted as P-gp inhibition (Wyen et al, 2008). Ritonavir alone at steady state (300 or 400 mg twice daily) increased digoxin AUC 1.4-to 1.9-fold (Ding et al, 2004;Kirby et al, 2012).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar conclusions were articulated previously (van Heeswijk et al, 2006) and also were reached using oral digoxin, considered to quantify primarily intestinal P-gp activity (Wyen et al, 2008). Ritonavir-lopinavir increased digoxin AUC and C max 1.8-and 1.6-fold, respectively, interpreted as P-gp inhibition (Wyen et al, 2008). Ritonavir alone at steady state (300 or 400 mg twice daily) increased digoxin AUC 1.4-to 1.9-fold (Ding et al, 2004;Kirby et al, 2012).…”
Section: Discussionsupporting
confidence: 87%
“…Changes in fexofenadine AUC caused by ritonavir-lopinavir are consistent with decreased fexofenadine intestinal efflux and acute inhibition of P-gp, with partial P-gp induction (yet continued net P-gp inhibition) on continuing exposure. Similar conclusions were articulated previously (van Heeswijk et al, 2006) and also were reached using oral digoxin, considered to quantify primarily intestinal P-gp activity (Wyen et al, 2008). Ritonavir-lopinavir increased digoxin AUC and C max 1.8-and 1.6-fold, respectively, interpreted as P-gp inhibition (Wyen et al, 2008).…”
Section: Discussionsupporting
confidence: 81%
“…After lopinavir/ritonavir, the geometric mean ratio for oxymorphone AUC was increased by 2.7-fold. Earlier studies have reported CYP2D6 inhibition during lopinavir/ritonavir [17,24].…”
Section: Pharmacodynamic Resultsmentioning
confidence: 98%
“…It is a substrate and inhibitor of CYP3A4 and to a lesser extent CYP2D6, and an inducer of CYP1A2, 2B6, 2C9 and 2C19 [23,24] which makes it prone to cytochrome P450-mediated interactions.…”
Section: Discussionmentioning
confidence: 99%
“…It is still equivocal whether long-term administration of ritonavir may also lead to a certain induction of CYP3A enzymes [15]. However, studies both in healthy volunteers [16] and patients [17] do not support CYP3A4 induction.…”
Section: Introductionmentioning
confidence: 99%